2014
DOI: 10.1111/bjh.13020
|View full text |Cite
|
Sign up to set email alerts
|

The bone marrow stromal compartment in multiple myeloma patients retains capability for osteogenic differentiation in vitro: defining the stromal defect in myeloma

Abstract: SummaryDefects in bone repair contribute to multiple myeloma (MM) bone disease. It is unknown whether this reflects failure of osteogenic differentiation from mesenchymal stromal cells (MSC), inherent stromal defects or mature cell dysfunction. We quantified the number of fibroblast colony-forming units (CFU-f) and osteoblast colony-forming units (CFU-ob) in freshly isolated bone marrow (BM) from healthy individuals (N = 10) and MM patients (N = 54). CFU-f and CFU-ob were present in MM BM, at comparable freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…The initial expansion in the stromal compartment is also in keeping with a recent report of an increase in nestin+ mesenchymal cells in the femoral bone marrow of NOG mice engrafted with MM cells (Iriuchishima et al, 2012). Our in vitro observation that MM cells induce increased cell cycling in pre-osteoblasts, and also in MSC (Kassen et al, 2014) suggest one explanation for these findings. We have also previously reported that MM cells directly increase osteoblast recruitment via an sIL6R dependent mechanism (Karadag et al, 2000), while Noll et al (2014) observed an increase in MSC numbers following tumour inoculation in the C57BL/KaLwRij murine myeloma model.…”
Section: Discussionsupporting
confidence: 91%
“…The initial expansion in the stromal compartment is also in keeping with a recent report of an increase in nestin+ mesenchymal cells in the femoral bone marrow of NOG mice engrafted with MM cells (Iriuchishima et al, 2012). Our in vitro observation that MM cells induce increased cell cycling in pre-osteoblasts, and also in MSC (Kassen et al, 2014) suggest one explanation for these findings. We have also previously reported that MM cells directly increase osteoblast recruitment via an sIL6R dependent mechanism (Karadag et al, 2000), while Noll et al (2014) observed an increase in MSC numbers following tumour inoculation in the C57BL/KaLwRij murine myeloma model.…”
Section: Discussionsupporting
confidence: 91%
“…OBs are derived from bone marrow MSCinduced to differentiate bymicro-environmental cues represented by cytokines and extracellular matrix components [56]. In MM patients, the osteogenic ability of mesenchymal progenitors to differentiate to mature OBs is disrupted [57][58][59], as evidenced by the decrease in the levels of Osterix, the major osteoblast transcriptional activator, and of the bone formation markers, i.e., ALPL and Collagen type I α1 chain [60][61][62]. In this context, we found that MM-EVs strongly downregulate the expression of these three markers actively participating in the inhibition of the first differentiation steps of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma is a common hematological malignancy mainly characterized by osteolytic lesions due to increased osteoclast number and activity and strongly decreased bone formation (Kassen et al, 2014). MSCs and osteoblasts support MM cells survival, proliferation, and progression (Azab et al, 2009; Reagan et al, 2014; Roccaro et al, 2014; Fairfield et al, 2016), while osteogenic differentiation is reduced in MM patients, which might be a putative strategy of MM cells to preserve cells (e.g., MSCs) necessary for their support (Corre et al, 2007; Reagan et al, 2014).…”
Section: Mscs Fate In Pathological Conditionsmentioning
confidence: 99%
“…Furthermore, they modulate osteoclast formation, survival, and resorptive activity through positive and negative regulatory molecules, among which RANKL and OPG are the iconic ones (Sharaf-Eldin et al, 2016). Finally, MSCs differentiation and secretory activities are relevant in skeletal pathologies such as multiple myeloma (MM), bone metastases, and bone marrow failure syndromes (BMFS), and their capacity to support and/or regulate hematopoiesis and cancer cells survival has been extensively described (Mundy, 2002; Kassen et al, 2014; David Roodman and Silbermann, 2015; Fairfield et al, 2016). …”
Section: Introductionmentioning
confidence: 99%